Psychological impact, coping strategies and social support of female survivors of domestic violence in Thohoyandou - Ramashia, Connie Livhuwani (My University, 2010)
Aims: The aim of the study was to determine the psychological impact, coping strategies and social support structures among female survivors of domestic violence. Participants: 112 female survivors of domestic violence who came to a trauma centre in Thohoyandou, Limpopo Province to seek help were selected as participants of the study. The participants in this study came from around Thohoyandou in the Thulamela Municipality district. The participants’ ages ranged from 15 to 65 years. Instruments: The questionnaire used was consisted of the following: 6 items covering the demographic variables of the participants such as age, marital status, level of education, employment status, number of years married, number of children; 37 items dealing with assessing the psychological problems i.e. depression and post-traumatic stress disorder; and 42 items dealing with seeking social support and coping strategies. Results: A significant number of the physically abused women were suffering from depression (z=2.8434, p<0.05). The results further revealed that a significant number of physically abused women had PTSD (z=15.31, p<0.05). The findings of this study showed that physically abused women tend to seek help from informal social support rather than formal social support (t=-8.572, df=104, p<0.05 with Mean score=1.99, SD= 1.236 for informal support and Mean score= .78, SD = .951 for formal support). This study further shown a significant difference on the use of escape-avoidance coping strategies compared to the use of many other coping strategies such as problem solving strategy (t= 4.065, df= 110, p<0.05 ); confrontive coping strategy (t= -.42232, df=111 , p<0,05), seeking support strategy (t= -8.740, df= 111, p<0.05) and self –control coping strategy (t= -5.451, df= 111, p<0.05). There was no significant difference between the use of escape-avoidance coping strategy and the use of distance coping strategy (t=.03348, df=111, p>0.05) and responsibility coping strategy (t=-.842, df=111, p>0.05). 11 • Conclusion: This study provides data that can be used to motivate the implementation of intervention programmes to address domestic violence against women. Such programmes must include the implementation of cost-effective intervention aimed at reducing the psychological harm caused by physical abuse. The study also highlighted the need for psychological treatment services. These services must present an important venue to identify and manage depression and PTSD amongst physically abused women. Intervention strategies must include imparting physically abused women with help seeking and coping skills.
Thesis (M.A.) (Clinical Psychology) --University of Limpopo, 2009.
Keywords: Domestic violence - Thohoyandou; Social support structures; Coping strategies; Female survivors